2(3x+1)=32
(2*3X)+(2*1)=32
6x+2=32
6X+2-2=32-2
6X=30
6X/6= 30/6
X=5
checking
2((3*5)+1)=32
2(15+1)=32
2(16)=32
2*16=32
32=32
2007-03-09 02:44:06
·
answer #1
·
answered by V H B 3
·
0⤊
0⤋
2(3x+1)=32
2(3x)+2(1)=32
6x+2=32
6x+2-2=32-2
6x=30
6x/6=30/6
x=5
Checking: 2[3(5)+1]
= 2(15+1)
=2 (16)=32
2007-03-09 02:45:10
·
answer #2
·
answered by b_ney26 3
·
0⤊
0⤋
2(3x + 1) = 32
3x + 1 = 32 / 2
3x + 1 = 16
3x = 16 - 1
3x = 15
x = 15 / 3
x = 5
Substitute x = 5 in the 1st eqn.
2(3 x 5 + 1) = 32
2(15 + 1) = 32
2(16) = 32
32 = 32
Q.E.D.
2007-03-09 02:43:58
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
2(3x=1)=32
x = 5
3*5=15
+1 = 16
times 2 = 32
enjoy
2007-03-09 02:43:37
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
2(3x + 1) = 32
6x + 2 = 32
6x = 30
x = 5
Check
2(3*5 + 1) = 2(15 + 1) = 2(16) = 32 Yup. All done.
HTH ☺
Doug
2007-03-09 02:42:12
·
answer #5
·
answered by doug_donaghue 7
·
1⤊
0⤋
2*3x = 6x
2*1 = 2
so, 6x + 2 = 32
6x = 32 - 2
6x = 30
so, x = 30/6
x = 5
check by plugging the 5 back into the original equation.
2(3(5) + 1) = 32
30 + 2 = 32...yep
2007-03-09 02:45:18
·
answer #6
·
answered by Sue O 2
·
0⤊
0⤋
2(3x+1)=32
3x+1=16
3x=15
x=5
put x=5 in eq
2(16)=32
2007-03-09 02:42:22
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
2*3x is 6x and 2*1 is 2, new equasion is 6x+2=32. 6x=32-2, the 6x=30 which is 30/6, final answer is x=5
2007-03-09 02:42:13
·
answer #8
·
answered by JASUFER 1
·
1⤊
0⤋
Divide both sides by two
2(3x + 1) = 32
3x + 1 = 16
subtract one from each side
3x = 15
divide by 3
x = 5
2007-03-09 02:42:47
·
answer #9
·
answered by RcknRllr 4
·
0⤊
0⤋
6x+2=32
6x+2-2=32-2
6x=30
x=5
(2(3(5)+2=32
2(15)+2=32
30+2=32
2007-03-09 02:41:19
·
answer #10
·
answered by Dave aka Spider Monkey 7
·
1⤊
0⤋